PEMBELAJARAN TEKNIK DASAR AKTING TEATER DALAM OLAH RASA MELALUI STRATEGI PEMBELAJARAN INOVATIF PADA SISWA KELAS VII DI SMP NEGERI 6 BOLIYOHUTO - Patila, Sartika; Pulukadang, Mimy A.; Semiaji, Trubus; Sitharesmi, Riana Diah; Djafar, Nurlia (SINERGI : Jurnal Riset Ilmiah, 2025)
This research was motivated by class VII students who were not yet able to perform basic theater acting techniques, especially in sports, so that when performing theater performances they were not optimal. So the researcher formulated the problem of how to learn the basic techniques of theater acting in taste through innovative learning strategies for class VII students at SMP Negeri 6 Boliyohuto. In implementing the learning of basic acting techniques in taste, researchers used innovative learning strategies. This strategy is to facilitate students in building their own knowledge in the context of a process of changing behavior towards a better one according to their individual potential. This research uses qualitative methods which are descriptive analysis. The data collection technique used is through a process of observation, interviews and documentation which will later be presented in the form of a research description. This learning was carried out within 2 months or 8 meetings. The sample that the researchers used was class VIII of SMP Negeri 6 Boliyohuto, totaling 16 students. Based on the results obtained from this research, it can be said to be successful. learning basic theater acting techniques in taste through innovative learning strategies for class VII students at SMP Negeri 6 Boliyohuto makes students more creative, innovative and active from the experiences they gain by studying outside the classroom and in the living environment around the students. From this experience, students are more active and diligent in studying than before.